KONSEP PENGETAHUAN IBN HAZM - ZUHRI ZUHRI (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
Studying knowledge is studying archeology of human creativities in understanding the process of dialectic. Therefare, knowledge is always promising and dynamic process of progression. In this context, Ibn Hazm adds the importance of values in the process. Axiological dimension in knowledge seems so strongly emphasized in the reading of Ibn Hazm descriptivly. However, the critical-hermeneutical reading of his ideas more fully and precisely shows how widespread Ibn Hazm emphasized the importance of the role and the epistemological dimension of knowledge. This article tries to present both these dimensions.